Psychosocial Impacts of the Colombian Conflict on Police and Military Members: Victims of Serious Breaches of International Humanitarian Law (2019)
Introduction: International Humanitarian Law (ihl) is a set of rules which seek to limit the effects of armed conflict. It protects persons who are not or are no longer participating in the hostilities and restricts the means and methods of war. Materials and methods: In 2014 and 2015, at the East Regional Office, about ten members of the National Army and the Police, involved in events that occurred in 1998 during guerrilla attacks in which they were deprived of their freedom and released months later, were assessed by psychiatry and forensic clinic. The majority were young men at the time of the events, belonging to indigenous or native population, with stress factors due to conflict-related circumstances. Results and discussion: The common psychosocial findings are presented, as well as the impact on lifestyle, culture and community. Physical harm is undocumented but described and perceived by the individuals examined. The particular situation of the Colombian armed conflict is described, with no reference at the international level. Conclusions: From forensic work it is necessary to recognize and make these situations visible to help to the recovery of the country’s psychosocial health, the harmonious repair of the social fabric, and the conservation of endangered ancestral cultures.